PANCASILA DAN SYARI’AT ISLAM SEBAGAI ASAS PEMBENTUKAN QANUN DI ACEH - Suganda, Delfi (SCAD Independent, 2014)
Pancasila as the state has to make sense of Pancasila as the basis for a set of governance. Aceh Qanun Laws and regulations are similar provincial regulations governing the administration of government and the Acehnese people. Aceh Qanun made based on laws and regulations that apply are compiled by the executive and legislature of Aceh. The position of Pancasila as the foundation of philosophy in Aceh Qanun is a legal norm in society aspired. Qanun can be used as the collective desire of the people of Aceh in carrying out day-to- day life, the Qanun expected through the implementation of the Acehnese people can feel the law is aspired for this. The implementation of Shari'a is a requirement of the Acehnese, and recognized by the State through Law No. 18 of 2001 on Special Autonomy and Law No. 11 Year 2006 on the Governing of Aceh. Applications of Shari’a in Aceh are in accordance with the first paragraph of the Pancasila as the practice of the precepts to five “justice for all Indonesian people